VD_FINDINFO AM 30/14 - 14/2015 vom 16. März 2015 - VD Tribunal cantonal (2015)
AM, ASSURANCE DES SOINS MÉDICAUX ET PHARMACEUTIQUES, TRAITEMENT HOSPITALIER | 24 LAMal, 25 LAMal, 32 LAMal, 49 LAMal, 50 LAMal, 56 LAMal, 57 LAMal, 7 al. 2 OPAS